Strategies for Determining Electron Yield Material Parameters for Spacecraft Charge Modeling - Phil Lundgreen; J. R. Dennison (Space Weather)
Abstract Accurate modeling of spacecraft charging is essential to mitigate well‐known and all‐too‐common deleterious and costly effects on spacecraft resulting from charging induced by interactions with the space plasma environment. This paper addresses how limited availability of electron emission and transport properties of spacecraft materials—in particular, secondary electron yields—and the wide ranges measured for such properties pose a critical issue for modeling spacecraft charging. It describes a materials charging database for electron emission properties under development, which facilitates more accurate spacecraft charge modeling when used in concert with the strategies outlined herein. These data and techniques provide tools for more accurate material selection, increased confidence in charge models, and a concomitant decrease in mission risk. They also allow better customization of models in response to prolonged space environment exposure and specific mission requirements, which may evolve materials properties.